PENGAMBILAN OLEORESIN DARI AMPAS JAHE (HASIL SAMPING PENYULINGAN MINYAK JAHE) DENGAN PROSES EKSTRAKSI - Faleh Setia Budi (TEKNIK, 2009)
During this time the ginger oil distillation waste are only used as fire wood for the distillation process. It ispredicted that this waste still contain oleoresin. Oleoresin is the mixture fixed oil (3 – 4 %), essential oil (1 – 3%), resin etc. This research aims to find the most affecting variable and the optimum operation condition inthe extraction processing oleoresin from ginger oil distillation waste. The research is planned to use thefactorial design method 2 levels and 3 independent variables i.e.: temperature (30-60 oC), time (2-6 hours)and solvent volume (300/150- 700/150) ml/gr the weight of ginger waste. The experiment quantities whichmust be carried out are 8 runs. The observed parameters are weight, density and refraction index. The threeindependent variables give positive effect/ increase the product and time is the most influential variables. Thenthe optimization process is carried out to get the optimum operation condition by varying the extraction time.The optimum operation condition of oleoresin extraction is 5.5 hours, temperature 60 oC and solvent volume700ml/150 gr the weight of ginger waste. The number of oleoresin which can be obtained volume 4.1 ml,weight oleoresin 2.7 grams, density 0.67 grams/ml, and refraction index 1.4744. GCMS analysis shows thatthe zingeberence content is 14.91%.